Co-existence of short- and long-range magnetic order in LaCo2P2. (6th December 2021) - Forslund, Ola Kenji; Andreica, Daniel; Ohta, Hiroto; Imai, Masaki; Michioka, Chishiro; Yoshimura, Kazuyoshi; Månsson, Martin; Sugiyama, Jun
Abstract: The ferromagnetic (FM) nature of the metallic LaCo2 P2 was investigated with the positive muon spin rotation, relaxation and resonance ( μ + SR) technique. Transverse and zero field μ + SR measurements revealed that the compound enters a long range FM ground state at T C ZF = 135.00 ( 1 ) K, consistent with previous studies. Based on the reported FM structure, the internal magnetic field was computed at the muon sites, which were predicted with first principles calculations. The computed result agree well with the experimental data. Moreover, although LaCo2 P2 is a paramagnet at higher temperatures T > 160 K, it enters a short range ordered (SRO) magnetic phase for T C ZF < T ≤ 160 K. Measurements below the vicinity of T C ZF revealed that the SRO phase co-exists with the long range FM order at temperatures 124 K ≤ T ≤ T C ZF . Such co-existence is an intrinsic property and may be explained by an interplay between spin and lattice degree of freedoms.